PENERAPAN KEDISIPLINAN KERJA DALAM MENINGKATKAN KOMITMEN ORGANISASIONAL PT PLN (PERSERO) UP3 MADIUN - Mei Mesra Bleszyni; Deilla Rahma Eka Wardani; Fery Setiawan (Universitas Muhammadiyah Ponorogo, 2026)
Work discipline is a crucial factor in improving employee performance and productivity, particularly in large-scale organizations such as PT PLN (Persero) UP3 Madiun. This independent work report aims to analyze the implementation of work discipline through attendance and punctuality, compliance with Standard Operating Procedures (SOP) and Occupational Safety and Health (OSH), as well as the utilization of digital technology to support work discipline. The methods used include direct observation, organizational data collection, and documentation during the activity. The results indicate that the implementation of digital attendance systems, AMS Korporat, and the Vendor Invoicing Portal (VIP) enhances work discipline, administrative efficiency, and the accuracy and transparency of work processes. Furthermore, compliance with SOP and OSH contributes to improving workplace safety, task effectiveness, and employee performance quality. Therefore, the synergy between work discipline, the implementation of SOP and OSH, and digital technology support is proven to improve employee performance and support the achievement of organizational goals effectively and sustainably. Keywords: Work Discipline, SOP, Occupational Safety and Health, Digital Technology, Employee Performance